INFORMATION ATTACKS OF THE INTERNET AND THE LEGAL BASIS FOR ITS PREVENTION - Imamova Umida Ismoil qizi (Journals Park Publishing, 2023)
The main source of norms regulating relations in the information sphere in our country is the Constitution of the Republic of Uzbekistan. The most important and promising plan and higher goals of the life of the state and society are also set out precisely in the Basic Law. In particular, information and related relations are also established in the chapter "personal rights and freedoms" of our basic law. All other legislation and legislative acts regulating relations in the field of information were adopted on the basis of our Constitution, which is our main law, and in order to harmonize the norms established in it. In this article, opinions and reflections on the information attacks of the internet and the legal basis of its acquisition are kept.
Keywords: internet, Information attacks, legal framework, state, society, Constitution, information security, norms, database.